2017
DOI: 10.1038/eye.2016.300
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for glaucoma: from the lab to the clinic

Abstract: Glaucoma, a leading cause of irreversible blindness worldwide, is often not diagnosed until many years after disease onset. Early and objective diagnostic measures are yet missing. Besides the main risk factor, an elevated intraocular pressure (IOP), age, sex, and ethnicity are known to affect disease progression and severity. Furthermore, oxidative stress, elevated glutamate concentrations, and an autoimmune component are considered possible risk factors. We could identify several potential proteomic biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…There are multiple risk factors associated with glaucoma [ 3 , 4 , 5 , 6 , 7 , 8 ], with elevated intraocular pressure (IOP) and aging being two of the more prominent ones [ 9 , 10 , 11 ]. Elevated IOP damages the axons of retinal ganglion cells (RGCs) that make up the optic nerve, eventually causing RGC dysfunction and loss and resulting in blindness [ 2 , 12 ]. Glaucoma is commonly treated with topically-applied IOP-lowering drugs that are well tolerated and effective in managing IOP [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple risk factors associated with glaucoma [ 3 , 4 , 5 , 6 , 7 , 8 ], with elevated intraocular pressure (IOP) and aging being two of the more prominent ones [ 9 , 10 , 11 ]. Elevated IOP damages the axons of retinal ganglion cells (RGCs) that make up the optic nerve, eventually causing RGC dysfunction and loss and resulting in blindness [ 2 , 12 ]. Glaucoma is commonly treated with topically-applied IOP-lowering drugs that are well tolerated and effective in managing IOP [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even when IOP is managed well, the disease can progress, resulting in significant vision loss. It is reported that more than 10% of patients become completely blind in at least one eye [ 3 , 12 , 13 , 14 ]. It is thus important to develop therapeutic approaches that directly protect RGCs in an IOP-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is a neurodegenerative disease characterized by retinal ganglion cells (RGC) death, typical visual field defect and eventual blindness [ 1 ]. Elevated intraocular pressure (IOP), aging, genetic, epigenetic and environmental factors are among a number of recognized risk factors for glaucoma [ 2 , 3 ]. Glaucoma is thus a progressive optic neuropathy with complex pathophysiology and RGC loss in glaucoma remains incompletely understood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific AAb patterns that reportedly depend on the glaucoma subtype are under investigation (36). As b2-agAAb adrenergic activity was observed in AH of POAG and SOAG and as these did not correlate with the routine glaucoma follow-up parameters, these data might indicate that b2-agAAb are involved in very early stages of glaucoma pathogenesis by shared pathophysiologic mechanisms.…”
Section: Discussionmentioning
confidence: 98%